Pengaruh Pendidikan, Pendapatan dan Kepadatan Penduduk Serta Distribusi Pendapatan Terhadap Permintaan Air PDAM di Kabupaten/Kota Provinsi Sumatera Barat - Riska Ratna Dewi Anugrah; Sri Ulfa Sentosa (Jurnal Kajian Ekonomi dan Pembangunan, 2023)
This study aims to examine the effect of Education, Income and PopulationDensity as well as Income Distribution on Water Demand in theRegencies/Cities of West Sumatra Province with the selected model being theRandom Effect Model (REM). The data used is panel data with a cross sectionof 18 regencies/cities and a 5 year time series from 2017 – 2021. The results ofthis study indicate that education has a significant positive effect on PDAMwater demand. The income and population density variables have nosignificant positive effect, while the income distribution variable has nosignificant negative effect on PDAM water demand.